Ultrasonic Measurement of Female Pelvic Reproductive Organs and Comparison of Body Mass Index(BMI)Between Fertile and Infertile Women - Ambreen Usmani ,Rashid Anjum , Muhammad Saeed (Journal of Rawalpindi Medical College, 2012)
Background: To determine the ultrasonic measurement of female pelvic reproductive organs and compare the BMI between fertile and infertile women Methods: In this descriptive study 120 women, 60 fertile and 60 infertile, subdivided into age groups 20 to 30, and 31 to 40, were included. Total ovarian volume (OV) was determined transabdominally (OV-TA) and transvaginally (OV-TV), antral follicle count (AFC), uterine size (US) and endometrial thickness (ENDO) performed transvaginally, and BMI calculated. Result: The ovarian reserve, uterine size, and BMI were strong indicators of fertility of a woman. Ovarian volume , uterine size and endometrial thickness were significantly increased in the younger fertile group as compared to the infertile group. Comparison of these variables showed a different pattern in the older fertile and infertile women. In the older fertile only the US was significantly larger than the infertile older group. Conclusion: Early measurement of these female pelvic reproductive organs can prevent primary infertility if the female is properly counseled regarding outcome of delaying conception.